Community structure of gastropods and bivalves associated in mangrove ecosystem at Pusung Cium Island, Seruway, Aceh Tamiang. Issue 1 (February 2021) - Dewiyanti, I; Harbi, M; ElRahimi, S A; Ulfah, M; Damora, A
Abstract: The purposes of the present study were to analyze the community structure of gastropods and bivalves as well as to analyze the relationship between the abundance of gastropods and bivalves within mangrove density in Pusung Cium Island, Seruway, Aceh Tamiang Regency. The research was conducted from October to November 2019. The method used in determining the location of the research station was Stratified Random Sampling based on the density of mangrove vegetation, the station 1 st, 2 nd, 3 rd were dense, medium, and rare categories, respectively. There were 4.67 ind/m 2 consisted of 3 species for bivalves class and 143.33 ind/m 2 species of gastropods class consisted of 41 species. The highest abundance was in station three, and the highest gastropods species abundance was Littorina angulifera (51.33 ind / m 2 ) and Saccostrea cucculata (1.33 ind / m 2 ) for bivalves class. Biological indices showed that the diversity index of gastropods and bivalves was high and ranged from 4.24 to 2.35, evenness and dominance indices were ranged from 0.44 to 0.79 and 0.20 to 0.21. Furthermore, the distribution pattern of gastropods and bivalves were uniform, random, and clumped. The correlation between the density of mangrove and abundance of gastropods-bivalves was weak and moderate and there was no significant correlation between the density of mangrove and abundance of biota aquatic (gastropods and bivalves) where Psig > 0.05. In conclusion, the community structure of gastropods and bivalves was in stable condition showed by high diversity index, moderate evenness index, and low dominance index.